ANALISIS PENGARUH INSENTIF PAJAK, TINGKAT PENDAPATAN, DAN DIGITALISASI TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI ERA PANDEMI COVID-19 : (Studi Kasus Wajib Pajak UMKM Wilayah Jakarta Timur) - Gloria Henriette; Annathasia.P. Erasashanti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This study aims to analyze the effects of tax incentives, income levels, and digitalization on MSME taxpayers’ compliance in the era of the COVID-19 pandemic in the East Jakarta area. This study used a quantitative method using a Likert measuring device and the data were primary data obtained from questionnaires filled out by MSME actors in the East Jakarta area which has in total population of 240.512 MSMEs, with sampling techniques using the purposive sample method. The determination of the number of samples is determined using the Slovin formula and gets the results of 100 respondents. The data analysis technique in this study was multiple regression using the SPSS version 26 application. The results of this study indicate that: Tax Incentives, Income Levels, and Digitalization have a significant and positive impact on Taxpayer Compliance